595 Risk Factors for Broncho-Pulmonary Dysplasia in Very-Low-Gestational-Age Infants. (October 2012) - Valls-i-Soler, A; Azpeitia, A; Hummler, H; Halliday, H
Abstract : Background: BPD is a severe condition that has decreased in severity but remains a major long-term adverse outcome of surviving Very Low Gestational Age (VLGA) infants. Aim: To determine the BPD rate and evaluate its predictive and associated factors. Methods: BPP (need for supplemental O2 at 36 wks CGA) rate and associated risk factors were analysed in a cohort of 24, 087 VLGA infants admitted from 2006 to 2010 to 174 EuroNeoNet NICUs. Non-parametric independent tests and logistic regression models were performed to predict BPD, using crude and adjusted odd ratios (OR) to determine perinatal and early neonatal associations. Predictive capacity was assessed by Hosmer-Lemeshow test and discrimination by area under ROC curve (AUC). Results: BPD was diagnosed in 16% (95%CI: (15.4%–16.1%)) of infants, who had significantly lower GA, BW and Apgar scores. They were more frequently male, from single pregnancies, more often had congenital anomalies, late-onset sepsis (LOS) (57.8% vs. 23.8%; OR:4.40; 95%CI:4.0–4.84) and symptomatic PDA (56.0 vs. 30.6%; OR:2.9; 95%CI:(2.6–3.2)). After adjusting for all BPD predictive perinatal risk factors (BW, GA, Apgar scores, gender and congenital anomalies (AUC:0.8, 95%CI:0.79–0.81), the factors strongly associated with BPD, other than BW and GA, were LOS (OR:2.54; 95% CI:2. 27–2.83) and symptomatic PDA (OR:1.54; 95%CI:1.38–1.73). Conclusion: In this large cohort of VLBW/VLGA, the rate of BPD was 16% (15.4–16.1%), strongly associated with GA and BW but also with LOS and symptomatic PDA. Acknowledgements: We thank patients and participating NICU's. EuroNeoNet is supported by the DGSANCO funded project EuroNeoStat (No. 2008–1311).